Social Distancing in the Septuagint as Ancient Medical Practice and Its Implications in the Gospel of Luke and Public Health - Godwin A. Etukumana (Pharos Journal of Theology, 2026)
The Septuagint (LXX), as one of the ancient texts, is marked by many intriguing aspects that prompted the society of the time to adopt certain practices centred on protecting the well-being and functionality of their society. One such intrigue was the development of a medical procedure to help separate people from one another in the event of a disease outbreak. Using social historical hermeneutics as a method of interpretation, it is observed that social distancing became a medical norm in the social, cultural, and economic contexts. The ancient Israelites, as shown in the LXX, had daily routines that did not hinder their ability to distance themselves from one another during disease outbreaks. Stipulations regarding distancing were known to everyone in their society. This article therefore examines how the concept of social distancing began in the LXX and why. It will also discuss the implications of understanding the Gospel of Luke, as Luke employs words similar to those found in the LXX. These lessons will be particularly relevant to present-day society, especially in public health.